Efficacy and safety of onabotulinumtoxinA injection in patients with refractory overactive bladder: First multicentric study in Turkish population - ONUR, AHMET RAHMİ (WILEY, 2018)
AimsTo investigate the efficacy and safety of intradetrusor onabotulinumtoxinA (onaBoNT-A) injection in patients with overactive bladder (OAB) refractory to antimuscarinic treatment. MethodsA total of 80 patients with OAB symptoms were enrolled in this prospective multicenter study and received 100U intradetrusor onaBoNT-A injection.The changes from baseline in the frequency of voiding, urge urinary incontinence (UI) and urge episodes, mean and maximum bladder capacities, uroflowmetry, post-void residual urine volume (PVR), quality of life score, and treatment benefit scale score were assessed. The need for a second injection,and treatment-related adverse events were also examined postoperatively. ResultsOnaBoNT-A injection significantly decreased the UI episodes(P=0.0001), the mean voiding frequency (P=0.0001), and the urgency episodes (P=0.0001) in the third month compared to baseline. Similarly, the mean bladder capacity, and maximal bladder capacity were increased (P<0,05). The quality of life scores improved by 57.1% compared to the pre-treatment rate (P=0,0001). No significant change was observed in the PVR or maximum flow rate. Urinary retention developed in 3 (3.75%) patients and urinary infection and transient hematuria were observed in five patients (6.25%) each. The UI episodes, voiding frequency and urgency episodes were significantly lower at the 9th month than at baseline (all P=0.0001). Overall 67% of the patients continued to experience benefits from the injection. Sixteen patients (20%) required a second injection in the third month. Eight patients were lost to follow-up at the last visit in the 9th month, and 34 of the remaining 56 patients required a second injection at the 9th month. Cumulatively, 50 (63%) patients needed re-injections. ConclusionsOur results demonstrated that the onaBoNT-A injection produced significant improvement in all OAB symptoms with a low incidence of treatment related adverse events.
Keywords: onabotulinumtoxinA; overactive bladder; quality of life; urinary incontinence; FEMALE URINARY-INCONTINENCE; DETRUSOR OVERACTIVITY; RISK-FACTORS; PREVALENCE